Reliability and validity of the positive mental health literacy scale in Chinese adolescents - Liu, Zhanfang; Yuan, Fangru; Zhao, Jin; Du, Jianzheng (Frontiers in Psychology, 2023)
Background and aim Mental health literacy (MHL) is not only the necessary knowledge and ability to promote mental health, but also an important determinant of mental health. Traditionally, the MHL Scale focuses on measuring knowledge and beliefs about mental disorders. In China, there are very few scales for assessing positive MHL. The present study aimed to evaluate the reliability and validity of a Chinese version of the Positive MHL Scale (MHPK-10) in Chinese adolescents. Methods Chinese adolescents (n = 1,247) completed the MHPK-10 online. The validation included the translation and cultural adaptation of the MHPK-10 original version into Chinese and assessment of its psychometric properties: reliability—test–retest and internal consistency, construct validity and criterion validity. Results Participant’s mean score on the revised positive MHL scale was 3.75 (SD = 0.69) which was a unidimensional scale. The correlation coefficients between each item and the total score were between 0.639 and 0.753. Scale item loadings ranged between 0.635 and 0.760 based on confirmatory factor analysis. Cronbach’s α coefficient of the scale was 0.869, and the test–retest intraclass correlation coefficient was 0.721 (p < 0.01). Criterion validity was assessed by comparing results of the revised MHPK-10 against those of other validated scales and resulting correlations ranged between 0.342 and 0.615. Conclusion The revised Chinese version of the MHPK-10 has sound reliability and validity and can be used to measure Chinese adolescents’ positive MHL.